Leveraging Potential of Nanotherapeutics in Management of Diabetic Foot Ulcer - Pandey, Supriya; Shaif, Mohammad; Ansari, Tarique M; Shamim, Arshiya; Kushwaha, Poonam (Experimental and Clinical Endocrinology & Diabetes, 2022)
Diabetic foot ulcers (DFUs) are the most common complications associated with diabetes mellitus. DFUs are displayed as open sores or wounds located on the bottom of the foot as a secondary complication of diabetes mellitus (DM). DFUs are associated with significant morbidity and mortality and can subsequently lead to hospitalization and lower limb amputation if not recognized and treated on time. An immense challenge to conventional treatments is caused by the chronic nature of diabetic foot syndrome and it has led to the emergence of nanotechnology-based therapeutics. The greatest advantages of these nanotherapeutics are their unique biological, chemical, and physical properties. The present review highlights the augmentation of bacterial infections relating to delayed healing of DFUs and the potential of nanotherapeutics such as polymeric nanoparticles, metallic nanoparticles, siRNA-based nanoparticles, lipid nanoparticles, and nanofibers in accelerating wound healing in diabetic foot ulcers.
Keywords: Nanotechnology; diabetes mellitus; diabetic foot ulcer; wound healing; pathophysiology; nanotherapeutics